Breakfast Cereal and Nutrition Education on Body Mass Index and Diet Quality in Elementary School Children: A Pilot Study - St-Onge Marie-Pierre; Buck Christine; L. Keller Kathleen (International Journal of Nutrition, 2015)
Objective: Skipping breakfast has been associated with an increased risk of obesity. This randomized controlled pilot study tested whether emphasizing breakfast consumption, in conjunction with nutrition counseling, would improve weight status and dietary quality in children. Design and Methods: Twenty children were recruited and randomized to a breakfast (BF, n=11) or control (n=9) intervention. Both groups received weekly group nutrition counseling for 12 wk but breakfast consumption was emphasized, and ready-to-eat (RTE) cereal provided, to BF only. Anthropometric measurements were taken weekly. Three-day food records were taken at baseline and endpoint. Results: Weight status did not change significantly, however, children in BF displayed an overall decrease in BMI (-1.0±5.1%) whereas children in the control group had an overall increase (1.1±7.2%) from baseline (P=0.52). Three-day food records (BF, n=6; control, n=5) revealed group x time interactions on total sugars (P=0.007), folate (P=0.05), vitamin B12 (P=0.03), sodium (P=0.05), niacin (P=0.009), and vitamin B6 (P=0.023). Except for sodium, BF had improvements in these nutrients relative to the control group. Conclusions: Preliminary data from this study show that the provision of RTE cereal with weekly nutrition counseling may positively affect intake of essential nutrients. The effects of breakfast consumption on weight status are still uncertain.
Keywords: Breakfast